Tingkat Pengetahuan dan Sikap Mahasiswa FK USU tentang Pentingnya Vaksinasi COVID-19 - Caroline, Chyntia (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2023)
Background. In the beginning of 2020, earth have been shocked by new pneumonia virus pandemic that start from Wuhan, Tiongkok. The virus have been rapidly spread and the disease is called Coronavirus disease 2019 (COVID-19). This research is conducted to survey student’s knowledge and attitude about the importance of COVID-19 vaccination. Purpose. This research of this study is to describe FK USU student’s knowledge about the importance of COVID-19 vaccine. Methods. Observational research without intervention or experiment with cross sectional design. Data will be collected by quesionaire. The number of sample that needed for this study are 88 sample and will be randomized using Simple Random Sampling method. Result. From this study, there are 50% of FK USU students with good knowledge, 40.4% with sufficient level of knowledge and 9.6% with low knowledge. Based on attitude level, there are 95.7% students with good level of attitude, 4.3% with sufficient level of attitude, while there are none of them with low level of attitude. Conclusion. Most of the USU’s Medical Student have good level of both knowledge and attitude towards COVID-19 Vaccine.